HRM strategies for sustainable performance: A focus on SDG-3 and SDG-8 in the logistics sector - Le, Tung-Thanh; Nguyen, Luan-Thanh; Pham, Nhi-Uyen Truong; Huynh, Tai Minh; Duc, Dang Thi Viet (International Journal of Management and Sustainability, 2025)
The logistics sector in Vietnam is a key driver of economic growth and is projected to become a billion-dollar industry. However, post-COVID-19 challenges, particularly a shortage of skilled employees, hinder its sustainable development. This study explores HRM solutions to address these challenges using the Person-Environment Fit Theory and Herzberg's Two-Factor Theory. Additionally, technological adoption (TAD) and employee well-being programs (EWP) are incorporated to examine their impact. Employing PLS-SEM and SPSS, the study analyzes employee perceptions of sustainable performance across different job levels. Findings reveal that improving work environments and employee well-being significantly enhance job satisfaction and sustainable outcomes. However, technological adoption shows a weaker impact than expected, with varying effects based on job levels. These insights highlight the need for tailored HRM strategies in the logistics sector. The study contributes to HRM literature by addressing workforce challenges specific to Vietnam and offers actionable insights for companies seeking to enhance employee satisfaction and commitment. Furthermore, it aligns with Sustainable Development Goals (SDGs) 3 (Good Health and Well-Being) and 8 (Decent Work and Economic Growth), providing a roadmap for integrating sustainability into HRM practices. The findings underscore the importance of effective HRM strategies in fostering a competitive and sustainable logistics industry.